Application of a three-surface kinematic hardening model to the repeated loading of thinly surfaced pavements - Hau, Kah Wai (2003)
Little effort has been made to apply the Critical State Soil Mechanics concept to the prediction of pavement response. The aim of this research is to apply soil mechanics principles, particularly the kinematic hardening concept, to the prediction of the response of lightly trafficked pavements to repeated loading. For this purpose, the finite element critical state program CRISP is used.